Analysis of Fraud Patterns in Islamic Banking Transactions: Strategies and Implementation of Prevention - Katsirin, Khairul (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
The research aims to analyze patterns of fraud in Sharia banking transactions and identify effective prevention strategies. The method used is a qualitative approach with case study data collection. The research findings reveal various common patterns of fraud, such as identity theft, document forgery, transaction manipulation, and misappropriation of funds. Factors such as weaknesses in the transaction system, weak security policies, and lack of employee training influence the occurrence of fraud. Prevention strategies that can be implemented include early detection systems, strict security policies, employee training, and cooperation with authorities. It is hoped that the research findings can assist Sharia banks in enhancing transaction security, protecting customers, and minimizing fraud risks.